Talking Stick Learning Model Assisted by Song Media: Influence on Social Science Knowledge Competence - Ika Sintya; Anak Agung Gede Agung (Universitas Pendidikan Ganesha, 2023)
Until now, students in elementary schools still have low competence in social science knowledge. It is caused by the applied learning model rather than by the characteristics of students, so the learning process feels boring. Therefore, this study aims to analyze the effect of applying the Talking Stick learning model assisted by song media (singing) on elementary school students' social studies knowledge competence. This type of research is quasi-experimental with a non-equivalent control group design. The population of this research is 753 students. The research sample was determined by cluster random sampling technique. The data collection method used in this research is the test method, and the instrument used is in the form of multiple-choice test questions. Research data were analyzed using descriptive and inferential statistical analysis techniques. Testing the hypothesis with the t-test showed a significant difference in the Talking Stick learning model assisted by song media (singing) on elementary school students' social studies knowledge competencies. Thus, the Talking Stick learning model assisted by song media (singing) affects increasing the competence of social studies knowledge of elementary school students. This research implies that it is necessary to continuously develop innovative learning models, such as the Talking Stick learning model assisted by song media (singing), so that it has a positive and significant effect on increasing the competence of social studies knowledge of elementary school students.